Australian Melolonthini (Coleoptera: Scarabaeidae: Melolonthinae): a sixth species of Pseudholophylla Blackburn, 1911, and notes on the other known species - Hutchinson, Paul M.; Allsopp, Peter G. (Zootaxa, 2021)
The genus Pseudholophylla Blackburn, 1911 (Coleoptera: Scarabaeidae: Melolonthinae: Melolonthini) is reviewed and males of a sixth species, P. hurai new species, are described and differentiated from males of the remaining species. The only known female, of P. lepidoptera Blackburn, 1912, is described and illustrated. The genus occurs across northern Australia in areas of savanna, hot semi-arid or hot desert and specimens are collected rarely.